Determination of essential nutrients and cadmium in the white quinoa and amaranth seeds - Bratovčić, Amra (Array, 2019)
Micronutrients are trace elements required in very small amounts in the diet. Metals such as copper (Cu), iron (Fe), and zinc (Zn) are essential nutrients that are required for various biochemical and physiological functions. Cadmium, which is considered as systemic toxicant that is known to induce multiple organ damage, even at lower levels of exposure, has been also determined. Therefore, in this paper the concentrations of Cu, Fe, Zn and Cd have been determined in the white quinoa and amaranth by ICP-MS analysis. Concentrations of all examined metals were higher in the amaranth. This research has shown that amaranth and white quinoa could be good sources of essential micronutrients. The concentration of cadmium in amaranth was very close to maximum permitted concentration in food.